2009
DOI: 10.3109/08039480903062950
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in a general hospital in Izhevsk, Russia

Abstract: Prevalence of depression was substantial but consistent with other studies. Taking into consideration associated factors, physicians can improve recognition and treatment of depression in medical inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The prevalence is close to the rate of 20.7% observed among the 323 adult inpatients in Izhevsk, Russia by using the Russian version of Mini International Neuropsychiatric Interview 5.0.0 and to the rate of 24.4% observed among 10,541 adult patients from 35 cities in Russia by using the CES-D scale [21,22]. International studies show that, despite its high prevalence, most depression cases are undiagnosed, untreated or under-treated around the world [2224]. It has been reported that 35.5% to 50.3% of the cases with serious mental disorders in developed countries and 76.3% to 85.4% in less-developed countries did not receive any treatment during the past year before the interview [23].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The prevalence is close to the rate of 20.7% observed among the 323 adult inpatients in Izhevsk, Russia by using the Russian version of Mini International Neuropsychiatric Interview 5.0.0 and to the rate of 24.4% observed among 10,541 adult patients from 35 cities in Russia by using the CES-D scale [21,22]. International studies show that, despite its high prevalence, most depression cases are undiagnosed, untreated or under-treated around the world [2224]. It has been reported that 35.5% to 50.3% of the cases with serious mental disorders in developed countries and 76.3% to 85.4% in less-developed countries did not receive any treatment during the past year before the interview [23].…”
Section: Discussionsupporting
confidence: 66%
“…Particularly in Russia, depression seems to be both under-investigated and undertreated [13]. Although depression has been observed to be associated with unprotected sex in other countries [5,7], to the best of our knowledge, no such association has been investigated in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Low rates of help seeking among persons with mental disorders have been widely reported [1]- [4]. One of the reasons cited for this phenomenon is poor understanding of mental disorders, their etiology, symptoms, treat-ment, and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The scenario is similar in Russia where recent studies have indicated the prevalence of lifetime and current depressive disorders to be 30% and 20.7%, respectively [4] with high percentages in both women (44%) and men (23%) [5]. Biochemical, endocrinal, neurophysiological, psychological and social-economical factors are known to play a role in the aetiology of depression.…”
Section: Introductionmentioning
confidence: 72%
“…Although fluvoxamine-based treatment is widely used for the management of depressive disorders in Russia, there are limited efficacy trials that are conducted in carefully selected populations under controlled conditions [4] [21]- [23]. Information on its efficacy and safety in treating depression under routine, uncontrolled settings, which is intended to have a greater generalizability in Russian population, is scarce.…”
Section: Introductionmentioning
confidence: 99%